Scientific foundations of vocational training of future grid automation engineers on the basis of causal learning - Rudevich, N. (Problems of Engineer-Pedagogical Education, 2019)
The paper defines the conceptual general scientific principles of vocational training of future grid automation engineers on the basis of causal learning. The research on the methodological system of vocational training of future engineers as a holistic object, in which goals, content, methods, means and forms of training are interrelated, has been conducted. It is determined that the ultimate goals of vocational training of future specialists should represent a system of competencies and should consist of intermediate goals for solving professional problems within the respective competencies on acquainting, conceptanalytical and productive-synthetic acquisition levels. It is established that the basic principle of constructing the content of vocational training of future engineers is to meet the requirement of a system of knowledge, characterized by the presence in the student's consciousness of structural-functional (content-logical) connections between individual elements of knowledge. Considering this, the content of vocational training of future grid automation engineers on the basis of the causal learning must ensure the development of the system of competencies used for solving professional tasks on the basis of the fundamental invariant causal chain of knowledge. It is established that the method of causal development of professional competency must serve as the basis of vocational training of future engineers. The paper substantiates a set of general scientific methods of cognition that should form the basis of the method of causal development of professional competency of future specialists, namely analysis, synthesis, synthesis, comparative, inductive, deductive, analogical, abstractive, specifying and modeling ones. It is established that vocational training of future engineers involves the development of special means in accordance with the method of causal development of professional competency. It is determined that the forms of vocational training of future grid automation engineers should represent a coherent system that, on the one hand, reflects the goals, content, methods and means of learning, and, on the other hand, determines the communicative interaction between the teacher and students, as well as between students themselves.